Recombination in vitro between herpes simplex virus type 1 a sequences. - Bruckner, R C (1992)
We have partially purified an activity from extracts of cells infected with herpes simplex virus type 1 that mediates recombination between repeated copies of the 317-base-pair a sequence of herpes simplex virus type 1. Recombination leads to deletion of a lacZ indicator gene situated between two directly repeated copies of the a sequence and is scored by transformation of lacZ- Escherichia coli. The two products of the reaction can be observed directly by restriction enzyme digestion and Southern blot analysis. The recombinase activity is also detectable, but at a lower level, in uninfected cell extracts. The DNA substrate must contain the two a sequences arranged in direct orientation to generate the lacZ deletion. However, when the a sequences are arranged in inverted orientation, an inversion results. A substrate with two homologous sequences of size and G + C content similar to the a sequence undergoes recombination at a much lower frequency. The reaction requires a divalent cation (Mg2+ or Mn2+) but not ATP or any other nucleoside triphosphate. The simple requirements and specificity for the a sequence suggest that the recombination may proceed by a site-specific mechanism.